Perfusion fraction derived from IVIM analysis of diffusion-weighted MRI in the assessment of placental vascular malperfusion antenatally. (4th March 2022) - Malmberg, Molly; Kragsterman, Ellen; Sinding, Marianne; Hansen, Ditte N.; Peters, David A.; Frøkjær, Jens B.; Petersen, Astrid C.; Sørensen, Anne
Abstract: Introduction: Specific placental pathologies that may impact fetal development, such as vascular malperfusion, are diagnosed postpartum. We aimed to evaluate if placental perfusion fraction ( f ) derived from intravoxel incoherent motion (IVIM) analysis of diffusion-weighted magnetic resonance imaging (DWI) can be used to identify specific types of placental vascular malperfusion antenatally. Method: 93 women who underwent placental DWI with multiple b-values at 23.9–41.3 week's gestation and postpartum histological examination were identified in the local placental MRI research database. Based on the placental examination, 44 were defined as normal controls and 49 cases had placental vascular malperfusion. Vascular malperfusion was subdivided into fetal vascular malperfusion (n = 13), maternal vascular malperfusion (n = 30) or both (n = 6). For each placenta, regions of interest were drawn on three placental slices and their mean f was estimated using intravoxel incoherence motion analysis. Results: In normal placentas mean f was 26.0 ± 4.6% (mean ± SD) and no linear correlation between f and gestational age was found, r = −0.05, p = 0.72. Placentas with fetal vascular malperfusion showed a significantly lower f (22.7 ± 4.4%) compared to normal controls, p = 0.03. In cases of maternal vascular malperfusion (25.2 ± 6.4%), no significant difference in f was revealed, p = 0.55. Conclusions: These results indicate that placental DWI-derived f may identify fetal vascular malperfusion in vivo. This study confirms a previous pilot study and provides initial evidence that fetal and maternal vascular malperfusion have different MRI signatures. Future studies are needed to further explore the clinical significance of this interesting finding. Highlights: Placental malperfusion is associated with placental dysfunction. Placental perfusion fraction ( f ) can be assessed by DWI MRI in vivo. f is reduced in placentas with histological evidence of fetal vascular malperfusion. Given a large intra-placental variation in f, the clinical relevance of the method may be limited.